Archiving fruits - Kamaruddin, Kamarulizwan; Mariapan, Manohar (University Putra Malaysia, 2012)
A Herbarium is a collection of dried plants or specimens of plants, that are systematically arranged, usually either geographically or alphabetically, for reference. Plant specimens are pressed in a plant press, which consists of a wooden frame, corrugated cardboard ventilators, blotter paper and folded paper, typically a newspaper. The objective of pressing plants is to extract moisture in the shortest period of time, preserving the morphological integrity of the plant and to yield material that can be readily mounted on herbarium paper for long-term storage.